Re-visiting community-based tourism intention in kelantan, malaysia: insights for tourists - Siti Nurliana Mat Jaffar; Siti Nurul Asyiqin Mohd Nor; Siti Nurul Athirah Hamizan; Siti Safwanah Maput (2022)
Community-based tourism is an important industry in helping to increase the interaction between the existing community-based diversity because it creates and strengthens the identity of a country. The purpose of this study is to identify factors that influence tourists to engage in community-based tourism in Kelantan, Malaysia. Therefore, this study examines the factors of tourist involvement directly and indirectly through the level of satisfaction at the tourist destination. Data will be collected from the cooperation of tourists to help provide an overview of the development of the community-based tourism industry in Kelantan, Malaysia. To investigate the involvement of tourists, this study will use the Statistical Package for Social Sciences (SPSS) which consists of descriptive analysis and correlation. In addition, the literature review proves that uniqueness, campaign and promotion, and accessibility are the main factors for tourists to start and continue to be involved with the community-based tourism industry. Uniqueness are the most significant factor of the independent variable is uniqueness between tourist involvement with community-based tourism in Kelantan, Malaysia.